Synthesis and characterization of inorganic nanomaterials for applications in energy storage and catalysis - Kulhavý, J (2022)
Inorganic nanomaterials are defined as materials with one or more dimension within 1 – 100 nm range. These materials possess unique optical, electronic, thermo-physical, physicochemical and mechanical properties, and represent intensively explored, studied and sought-after commodities for a large variety of applications and manufacturing processes. Heterogeneous catalysts are vital for many industrial processes and often take advantage of the unique reactivity properties of nanomaterials, while battery electrode materials composed of nanomaterials are explored to solve current limitations with higher power densities via stable rapid ion and electron transport, and with high energy density via maximization of the charge storage capability. This thesis provides an insight into synthetic methods, detailed characterization and properties study, and exemplary applications of engineered 2D MoS2 nanomaterials in Li and Na ion batteries, palladium nanoparticles supported on 2D MoS2 nanosheets as heterogeneous catalysts in Suzuki and Heck C-C coupling and 1-pentyne hydrogenation reactions and sulphate functionalized titanium oxide nanoparticles as solid superacid catalysts in the esterification reaction of levulinic acid and pyruvaldehyde Cannizzaro reactions.